Analysis of Laissez-Faire Leadership Practice on Performance of Logistics Industry, Dubai, United Arab Emirates - Mbuvi, Charles Kiilu; Mandere, Evans Nyamboga; Kilei, Peary (The Journal of Accounting and Management, 2025)
The modern business environment requires effective leadership practice. Laissez-faire leadership is a delegative practice, that grants employees’ autonomy with minimal supervision, assuming they are competent, self-driven specialists. This study examined the impact of laissez-faire leadership practice on Dubai’s logistics industry’s performance. Using a cross-sectional survey and descriptive research design, primary data was collected via structured questionnaires, while secondary data came from respective companies’ websites and reliable online sources. Data analysis involved descriptive and inferential statistics. Linear regression found a statistically significant relationship between laissez-faire leadership practice and performance of Dubai’s logistics industry. Key performance indicators included global logistics hub, world-class business infrastructure, and increased international sales. The study concluded that adopting laissez-faire leadership practice significantly enhanced organizational performance in Dubai’s logistics sector, reinforcing Dubai’s role as a global logistics leader.